You make me sick!. (1st October 2020) - Çıngıl Barış, Çiğdem
Abstract: A virus is a small, infectious particle that lives inside a host. Today, viruses have an important role in our daily life. The reason for this is that viruses, including coronavirus (COVID-19), are affecting many people in the world. The most important measure that can be taken to stop the spread of the disease will be self-taken measures along with increased the awareness of individuals. Schools, and especially teachers, play a vital role in this. Sharing accurate information and science-based facts about viruses will help reduce students' fears and anxieties about the disease and support their ability to cope with its effects on their lives. The main purpose of this activity is to help students learn about viruses, how they spread and how to prevent them from spreading. The 5E (Engagement, Exploration, Explanation, Elaboration, and Evaluation) learning model is used. The organization of these activities leads to provide research and constructivist learning rather than a traditional laboratory activity series. Also, students have fun during these activities.